Universal Single-Probe RT-PCR Assay for Diagnosis of Dengue Virus Infections - Erik Alm; Birgitta Lesko; Gunnel Lindegren; Clas Ahlm; Sandra Söderholm; Kerstin I. Falk; Nina Lagerqvist (2014)
Background Dengue is a mosquito-borne viral disease that has become more prevalent in the last few decades. Most patients are viremic when they present with symptoms, and early diagnosis of dengue is important in preventing severe clinical complications associated with this disease and also represents a key factor in differential diagnosis. Here, we designed and validated a hydrolysis-probe-based one-step real-time RT-PCR assay that targets the genomes of dengue virus serotypes 1–4. Methodology/Principal Findings The primers and probe used in our RT-PCR assay were designed to target the 3′ untranslated region of all complete genome sequences of dengue virus available in GenBank (n = 3,305). Performance of the assay was evaluated using in vitro transcribed RNA, laboratory-adapted virus strains, external control panels, and clinical specimens. The linear dynamic range was found to be 104–1011 GCE/mL, and the detection limit was between 6.0×102 and 1.1×103 GCE/mL depending on target sequence. The assay did not cross-react with human RNA, nor did it produce false-positive results for other human pathogenic flaviviruses or clinically important etiological agents of febrile illnesses. We used clinical serum samples obtained from returning travelers with dengue-compatible symptomatology (n = 163) to evaluate the diagnostic relevance of our assay, and laboratory diagnosis performed by the RT-PCR assay had 100% positive agreement with diagnosis performed by NS1 antigen detection. In a retrospective evaluation including 60 archived serum samples collected from confirmed dengue cases 1–9 days after disease onset, the RT-PCR assay detected viral RNA up to 9 days after appearance of symptoms. Conclusions/Significance The validation of the RT-PCR assay presented here indicates that this technique can be a reliable diagnostic tool, and hence we suggest that it be introduced as the method of choice during the first 5 days of dengue symptoms.